2016
DOI: 10.24036/jh.v15i2.6514
|View full text |Cite
|
Sign up to set email alerts
|

The Shift of Minangkabau Cultural Values in the Novel Persiden by Wisran Hadi (A Genetic Structuralism Approach)

Abstract: This study aims obtaining an understanding of the shifting of Minangkabau cultural values. It uses qualitative descriptive through genetic structuralism approach. Issues covered are: (1) description of the intrinsic elements; (2) shift in cultural values in terms of social structure; (3) shift in cultural values in terms of the author's view. Data are sentences or paragraphs, dialogue and monologue taken from the novel Persiden written by Wisran Hadi. The intrinsic elements are themes, plots, characters, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To understand Indigo through novel, nine relevant studies were found, among of them are: 1) a research article "The Shift of Minangkabau Cultural Values In The Novel By Wisran Hadi (A Genetic Structuralism Approach)" by Delia Putri that produces three conclusions: the intrinsic elements, included topic, slot, character, and setting; shift in cultural values in terms of social structure; and shift in cultural values in terms of the author's view (Putri, 2016); 2) a research article "Gender Perspective In The Novels "Padang Bulan"and "Cinta di Dalam Gelas" By Andrea Hirata: A Study of Structure and Feminism Literary Criticism and Its Relevance as The Literature Reading Materials for High Schools" by Tanita Liasna and Khairil Ansari that produces three conclusions: structure in bilogy novel "Padang Bulan" and "Cinta di Dalam Gelas" included topic, character, setting, point of view, and message; gender perspective that appeared in bilogy novel "Padang Bulan" and "Cinta di Dalam Gelas" that is equality of gender and inequity of gender; and bilogy novel "Padang Bulan" and "Cinta di Dalam Gelas" is very relevant as literature material in Senior High School (Liasna & Ansari, 2016); 3) a research article "Plot In A Collection Of Short Stories "Sakinah Bersamamu" Works Of Asma Nadia With Feminimism Analysis" by Noermanzah that have two forms, plot forward and plot backward, with the stages of starting point with a simple introduction, conflict, recognition of conflict, complication, denouement, and resolution (Noermanzah, 2017); 4) a research article "Humanity Degradation In The Novels Written By Minangkabau Ethnics" by Yasnur Asri, Zulfadli, and M. Ismail Nst that produce conclusion: six forms of human degradation that are humanity degradation by social class, humanity degrade through human as material, humanity degradation through violence, humanity degradation community based social function, humanity degradation by power, and humanity degradation by matrilineal culture system (Asri, Zulfadli, & Ismail Nst, 2016); 5) a research article "Representation Of Japanese Post-Colonial Experience In The Year Of 1942-1945 Based on Pramoedya Ananta Toer's Novel "Perburuan" by Rifqia Kartika Ningrum, Herman J. Waluyo, and Retno Winarni that produces conclusion is through the representation of characters in the novel Perburuan found the forms of resistance, betrayal, and characteristic's selfdoubts (Ningrum, Waluyo, & Winarni, 2017); 6) a research article "Psychological Interpretation of The Novel Stranger by Camus" by R. Gnanasekaran that produces conclusion is Meursault's character in The Stranger's novel in considered a monster in a society based on the novel, when in fact the Meursault is a figure who maintains his dignity and is a modest man (Gnanasekaran, 2014); 7) a research article "Stream of Consciousness Technique and Modern Novel: Psychological and Methodological Perspectives on Language Learning" by Mirjana Lončar-Vynović that produces conclusion that psychology has an important role to the students's unconsciousness in the process of studying in the novel(Lončar-Vynović, 2013); 8) a research article "Comparative Study on Individual's Performance Orientation and Their Aura Life Color" by Priyal and Ramkumar resulting in the study that indigo, blue, and violet aura has an ONLINE ISSN 2928-3936 UNP UNP UNP UNP JOURNALS JOURNALS JOURNALS JOURNALS aura of good loyalty and orientation …”
Section: Introductionmentioning
confidence: 99%
“…To understand Indigo through novel, nine relevant studies were found, among of them are: 1) a research article "The Shift of Minangkabau Cultural Values In The Novel By Wisran Hadi (A Genetic Structuralism Approach)" by Delia Putri that produces three conclusions: the intrinsic elements, included topic, slot, character, and setting; shift in cultural values in terms of social structure; and shift in cultural values in terms of the author's view (Putri, 2016); 2) a research article "Gender Perspective In The Novels "Padang Bulan"and "Cinta di Dalam Gelas" By Andrea Hirata: A Study of Structure and Feminism Literary Criticism and Its Relevance as The Literature Reading Materials for High Schools" by Tanita Liasna and Khairil Ansari that produces three conclusions: structure in bilogy novel "Padang Bulan" and "Cinta di Dalam Gelas" included topic, character, setting, point of view, and message; gender perspective that appeared in bilogy novel "Padang Bulan" and "Cinta di Dalam Gelas" that is equality of gender and inequity of gender; and bilogy novel "Padang Bulan" and "Cinta di Dalam Gelas" is very relevant as literature material in Senior High School (Liasna & Ansari, 2016); 3) a research article "Plot In A Collection Of Short Stories "Sakinah Bersamamu" Works Of Asma Nadia With Feminimism Analysis" by Noermanzah that have two forms, plot forward and plot backward, with the stages of starting point with a simple introduction, conflict, recognition of conflict, complication, denouement, and resolution (Noermanzah, 2017); 4) a research article "Humanity Degradation In The Novels Written By Minangkabau Ethnics" by Yasnur Asri, Zulfadli, and M. Ismail Nst that produce conclusion: six forms of human degradation that are humanity degradation by social class, humanity degrade through human as material, humanity degradation through violence, humanity degradation community based social function, humanity degradation by power, and humanity degradation by matrilineal culture system (Asri, Zulfadli, & Ismail Nst, 2016); 5) a research article "Representation Of Japanese Post-Colonial Experience In The Year Of 1942-1945 Based on Pramoedya Ananta Toer's Novel "Perburuan" by Rifqia Kartika Ningrum, Herman J. Waluyo, and Retno Winarni that produces conclusion is through the representation of characters in the novel Perburuan found the forms of resistance, betrayal, and characteristic's selfdoubts (Ningrum, Waluyo, & Winarni, 2017); 6) a research article "Psychological Interpretation of The Novel Stranger by Camus" by R. Gnanasekaran that produces conclusion is Meursault's character in The Stranger's novel in considered a monster in a society based on the novel, when in fact the Meursault is a figure who maintains his dignity and is a modest man (Gnanasekaran, 2014); 7) a research article "Stream of Consciousness Technique and Modern Novel: Psychological and Methodological Perspectives on Language Learning" by Mirjana Lončar-Vynović that produces conclusion that psychology has an important role to the students's unconsciousness in the process of studying in the novel(Lončar-Vynović, 2013); 8) a research article "Comparative Study on Individual's Performance Orientation and Their Aura Life Color" by Priyal and Ramkumar resulting in the study that indigo, blue, and violet aura has an ONLINE ISSN 2928-3936 UNP UNP UNP UNP JOURNALS JOURNALS JOURNALS JOURNALS aura of good loyalty and orientation …”
Section: Introductionmentioning
confidence: 99%